2006
DOI: 10.1115/1.2217957
|View full text |Cite
|
Sign up to set email alerts
|

Physical-Chemical and Thermodynamic Analyses of Ethanol Steam Reforming for Hydrogen Production

Abstract: Steam reforming is the most usual method of hydrogen production due to its high production efficiency and technological maturity. The use of ethanol for this purpose is an interesting option because it is a renewable and environmentally friendly fuel. The objective of this article is to present the physical-chemical, thermodynamic, and exergetic analysis of a steam reformer of ethanol, in order to produce 0.7Nm3∕h of hydrogen as feedstock of a 1kW PEMFC. The global reaction of ethanol is considered. Superheate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Compression and intercooling also require a significant amount of energy input per unit of hydrogen produced. In contrast, when liquid ammonia is expanded, energy can be harnessed through expansion, thus partially recovering the compression power [61,62]. The plantwide exergy efficiency (i.e., without considering the supply chain efficiency), shown in Figure 12, also exhibits this trend.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Compression and intercooling also require a significant amount of energy input per unit of hydrogen produced. In contrast, when liquid ammonia is expanded, energy can be harnessed through expansion, thus partially recovering the compression power [61,62]. The plantwide exergy efficiency (i.e., without considering the supply chain efficiency), shown in Figure 12, also exhibits this trend.…”
Section: Resultsmentioning
confidence: 87%
“…A way to help reduce the amount of exergy destroyed in Thomass-based production plants is to employ better technologies to remove bagasse moisture as well as implement hot catalytic cleaning of the syngas, thus avoiding the waste heat in the water scrubbing section. An increase in the gasifier pressures would also help avoid excessive compression power consumption [61].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 and then the oxidation state of all such atoms at a given reaction step is summed (Ox i ) and the difference ΔOx i = Ox i − Ox target is found. Should both ΔOx i and ΔOx i−1 be positive (or both negative) and |ΔOx i | > |ΔOx i−1 | a penalty for step i will be applied according to eqn (13) as an oxidation or reduction that needs to subsequently be corrected has taken place. If, however both ΔOx i and ΔOx i−1 are of opposite signs an overshoot has taken place and the penalty will be given by eqn (14).…”
Section: Papermentioning
confidence: 99%
“…However, reported data on exergy costs and CO2 emission cost of various fuels [47][48][49][50][51] have shown that a small part of the cumulative unit exergy costs of natural gas and petroleum derivatives corresponds to renewable sources and, thus, it must be accounted for if a fair level playing field for comparative assessments with other syngas and ammonia production technologies is intended. For instance, other scenarios, including the syngas production by using the steam reforming of ethanol, have earned more attention in Brazil, mainly due to its well-established sugar cane ethanol economy [111][112][113][114][115]. Thus, apart from the fossil-based ammonia production process, future works on ethanol-based ammonia production may offer a more interesting opportunity to highlight the importance of the allocation of the renewable unit exergy costs and CO2 emission cost, including those associated to the upstream processing stages of the sugar cane.…”
Section: Cumulative Unit Exergy Costs and Co2 Emission Costmentioning
confidence: 99%